Time-Dependent Quantum Dynamics Study of the $F+CD_4→DF+CD_3$ Reaction (Journal of Atomic and Molecular Sciences, 2015)
A four-degrees-of-freedom, time-dependent quantum wave packet propagationmethod is employed to study the $F+CD_4→DF+CD_3$ reaction. The calculationsshow a common resonance peak appears in the reaction probabilities, whichverifies the prediction of such resonance from experiment. For $F+CD_4,$ the vibrationalexcitations of the $C$-$H$ stretching mode enhance the reactivity, whereas the $C$-$X$ umbrella vibrational excitations hinder the reaction; and the translational energy ismore effective than vibrational energy at very lower collision energy, and less effectivethan the vibrational energy at most energy range. So for this endoergic early barrierreaction, the Polanyi rules cannot be extended to this poly-atomic reaction except atvery low collision energy.